2016
DOI: 10.1021/acsami.6b04104
|View full text |Cite
|
Sign up to set email alerts
|

Local Time-Dependent Charging in a Perovskite Solar Cell

Abstract: Efficient charge extraction within solar cells explicitly depends on the optimization of the internal interfaces. Potential barriers, unbalanced charge extraction, and interfacial trap states can prevent cells from reaching high power conversion efficiencies. In the case of perovskite solar cells, slow processes happening on time scales of seconds cause hysteresis in the current-voltage characteristics. In this work, we localized and investigated these slow processes using frequency-modulation Kelvin probe for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
129
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(139 citation statements)
references
References 57 publications
10
129
0
Order By: Relevance
“…In this case, however, photogenerated electrons and holes collected in the valleys rapidly recombine due to high rates of recombination in the n- and p-type contact regions, and the electric field associated with ionic charge remains unscreened. Since the presence of the photovoltage partially negates the built-in potential, the concentration of ionic defects at the contacts decreases as the defects migrate away, until the E-field in the bulk of the cell is once again zero, consistent with recent scanning Kelvin probe observations44. At this point, the V oc reaches a plateau.…”
Section: Resultssupporting
confidence: 86%
“…In this case, however, photogenerated electrons and holes collected in the valleys rapidly recombine due to high rates of recombination in the n- and p-type contact regions, and the electric field associated with ionic charge remains unscreened. Since the presence of the photovoltage partially negates the built-in potential, the concentration of ionic defects at the contacts decreases as the defects migrate away, until the E-field in the bulk of the cell is once again zero, consistent with recent scanning Kelvin probe observations44. At this point, the V oc reaches a plateau.…”
Section: Resultssupporting
confidence: 86%
“…Thermodynamically activated PCBM molecules diffuse into the bulk of perovskite, passivating traps at surface and grain boundary (GB), thus enhancing the charge transport and charge extraction. Kelvin probe force microscopy (KPFM) [61,62], as a powerful tool to investigate the charge distribution, provides direct evidences of charge trapping and detrapping process.…”
Section: Charge Trapping/detrappingmentioning
confidence: 99%
“…[25][26][27] Several studies indicated that, regardless of particular architecture and constituents within the PSCs, X defects migrate and reversibly accumulate within the perovskite lattice in narrow Debye layers at the interfaces with the charge selective contacts. 19,[28][29][30][31][32][33][34] Depending on voltage and light bias conditioning, accumulation of ions (and their vacancies) partially screens the built-in electric field and possibly creates interfacial electronic trap states, which reduce the charge extraction efficiency. 25,30,31,[34][35][36][37][38][39][40][41][42][43] Ion migration on timescales from 10 -1 to 10 2 s has been widely investigated to explain the hysteresis of current density-voltage (J-V) curves.…”
Section: Introductionmentioning
confidence: 99%